An agent-based workflow for evaluating interpersonal visibility in healthcare environment - Hao Yuan; Ying Zhou (Journal of Asian Architecture and Building Engineering)
Healthcare environment design evaluation (HEDE) can help create a safe environment, and interpersonal visibility among users is a key metric for assessing the safety of HEDE due to its role in caregiving observation. Traditional tools for visibility evaluation mainly focus on physical obstructions, neglecting the impact of the user’s mobility behavior, which is common in the healthcare environment. To address this challenge, this study developed a five-step workflow to evaluating interpersonal visibility among mobile users in healthcare environment: 1) collection of empirical behavior data from users; 2) construction of user journeys; 3) validation of agent-based simulation (ABS) reliability; 4) utilization of ABS to simulate user behavior in a virtual environment; and 5) computation of total visibility duration and time intervals between users using the parametric computation tool. This workflow was tested in 25 long-term care facilities for the elderly with dementia and subsequently evaluated by experts. The evaluation results confirm the effectiveness of this workflow. The core contribution and novelty of this workflow lie in its integration of ABS and parametric computation, which enables the evaluation of interpersonal visibility among mobile users, thereby contributing to the safety of the healthcare environment.